Simultaneous analysis of haloacetonitriles, haloacetamides and halonitromethanes in chlorinated waters by gas chromatography-mass spectrometry - Carter, R.; Liew, D.; West, N.; Heitz, Anna; Joll, Cynthia (Elsevier, 2019)
Nitrogenous classes of disinfection by-products (DBPs), such as haloacetamides (HAAms), haloacetonitriles (HANs) and halonitromethanes (HNMs), while generally present at lower concentrations in disinfected waters than carbonaceous DBPs, such as trihalomethanes or haloacetic acids, have been shown to be more detrimental to human health. While several methods have been shown to be suitable for the analysis of some nitrogenous DBPs (N-DBPs) in disinfected waters, many are unable to quantify HAAms, the most detrimental to health of these three N-DBP classes. Here, we report the first method for the simultaneous analysis of twenty-five N-DBPs (nine HANs, nine HNMs and seven HAAms) in disinfected waters using liquid-liquid extraction followed by gas chromatography-mass spectrometry. The use of a programmable temperature vaporiser injector minimises degradation of the thermally labile HNMs, while avoiding the concomitant decreases in HANs and HAAms which occur when using lower injector temperatures. Extraction parameters, including sample pH, solvent volume, salt addition and sample pre-concentration, were investigated to determine the optimal conditions across all target N-DBPs. Good detection limits were achieved for all analytes (0.8–1.7 µg L-1) and both laboratory and instrumental runtimes were significantly reduced compared to previous methods. The method was validated for the analysis of N-DBPs in drinking, swimming pool and spa waters, and concentrations of up to 41 µg L-1 of some N-DBPs were measured in some pools.